A Proposed Accounting Model Depend on Mixed Based Costing (MBC) Technique for Risks Assessment and Improving the Quality of Cost Reports: An Applied Study in Al-Rasheed Bank - Ali Abdul-Hussein Hani Al-Zameli (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2026)
The research aims to build a model accounting proposal depends on technique costs on basis the blending (MBC) and a statement of its impact on assessment Risks and strengthening accuracy reports cost in sector the banker, with the focus on study Applied in bank Al-Rashid. It depends technique Proposed on to merge several Accounting Methods like Costs built on activities (ABC) and Traditional costs, To reach to information more accurately and comprehensively on centers cost and Activities Banking. and it has sought Search for a test relationship between application this is amazing Technique and improving practical to set Analysis of operational risks And Finance, In addition to evaluation bezel its contribution in to support decision takers inside the Bank. It was completed. Use Curriculum Descriptive Analytical, Supported next to applied included analysis Data Finance Interviews with Officials Cost and risks in bank Al-Rashid. The research reached several conclusions, the most important of which were: that application technique Costs on basis Mixing Contributes In a way effective in discovery on Costs hidden and improving its distribution accurately on Activities Which Reflected Positively on practical assessment Risks, And it strengthens from quality reports Finance and Accounting. And it has Recommended Search Necessity adoption This is amazing Technique In a wider way in Iraqi banks, Training Staff Accounting on Using it In the form The ideal.